Second language teacher education in the expanding circle: The EFL methodology course in Chile - Martin, Annjeanette (Colombian Applied Linguistics Journal, 2016)
With the growth of EFL instruction worldwide, there has been increasing interest in how English teachers are prepared, yet little research has addressed these programs in foreign contexts. As part of pedagogical formation, methodology courses are considered key in developing both ‘received’ and ‘experiential’ teacher knowledge. Inspired by previous research, the current descriptive study analyzes the pedagogical content of methodology courses in EFL teacher programs in 16 Chilean universities and addresses the perceptions of methodology instructors by means of a questionnaire and an interview. Results highlight similarities and differences among programs, some considerations in designing methodology courses, and the challenges in articulating the connection between theory and practice.